MiR-26a enhances colorectal cancer cell growth by targeting RREB1 deacetylation to activate AKT-mediated glycolysis. (28th November 2021) - Chen, Bing; Deng, Ya-nan; Wang, Xixi; Xia, Zijing; He, Yu; Zhang, Peng; Syed, Samina Ejaz; Li, Qiu; Liang, Shufang
Abstract: We previously reported the inhibitory effects of microRNA-26a (miR-26a) on the conversion of pyruvate to acetyl coenzyme A in glucose metabolism by directly targeting pyruvate dehydrogenase protein X component in colorectal cancer (CRC) cells (Chen B et al., BMC Cancer 2014). Here, using microRNA in situ hybridization, we confirmed that miR-26a levels were elevated in 77 human CRC tissue samples and further investigated the key miR-26a-mediated metabolic regulation elements and signaling pathways in CRC cells through quantitative proteomic dissection combined with cancer cell biology and biochemical loss-of-function analysis. We found that AKT transcription signaling was a target pathway via miR-26a-mediated deacetylation modification of Ras-responsive element-binding protein 1 (RREB1) at the Lys-60 residue. miR-26a improved the deacetylation level of RREB1, thus contributing to RREB1 binding to the AKT1 promoter to activate AKT transcription and its related signaling pathway in glycolysis. Moreover, miR-26a promoted CRC tumorigenesis in CRC cells and subcutaneous xenograft mice. Thus, miR-26a is a key regulator of CRC tumorigenesis that mediates the deacetylation modification of RREB1 to enhance AKT1 transcription and downstream target gene expression in glycolysis for CRC growth. Highlights: miR-26a causes expression changes of key proteins/enzymes which involve in glycolysis and acetyl-CoA metabolism. miR-26a mediates colorectal cancer cell glycolysis by AKT signaling pathway. miR-26a enhances deacetylation modification of RREB1 at Lys60 residue via reducing the acetyl-CoA level. RREB1 deacetylation contributes to AKT1 promoter binding to activate AKT transcription and glycolysis signaling pathway. miR-26a promotes colorectal cancer tumorigenesis in vitro and in vivo .